2020
DOI: 10.9755/ejfa.2020.v32.i11.2190
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Antibiotic Residues And Antibacterial Activity Of The Endemic Spurge Honey (Euphorbia Resinifera O. Berg) From Morocco

Abstract: Antibiotic-resistant bacteria continue to be of major health concern worldwide. In recent years, several reports and scientific articles claim the contamination of honey by antibiotics, detectable concentrations of antibiotic residues in honey are illegal. They, may cause hypersensitivity or resistance to drug therapy in humans, and are perceived by consumers as undesirable. In this sense, the purpose of this work was to examine the antibacterial activity of the Euphorbia resinifera (E. resinifera) honey again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Beyond the nutritive aspect of honeys, Euphorbia honey has been target of study due to its economical importance in Morocco, thereby investigation has increased on the melissopalynological and physico-chemical characterization [4][5][6][7][8] and biological properties with potential application on human health [9][10][11]. Anti-inflammatory, analgesic and antimicrobial properties have been attributed to Euphorbia honeys along with the ability to promote wound healing, nevertheless, the majority of works has been focused on the anti-microbial activity [9][10][11], and much less, antioxidant activity [12]. More recently, our team compared the antioxidant activity and some enzyme inhibitory activities of Euphorbia officinarum, E. resinifera plants with those of the respective two monofloral honeys [13].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the nutritive aspect of honeys, Euphorbia honey has been target of study due to its economical importance in Morocco, thereby investigation has increased on the melissopalynological and physico-chemical characterization [4][5][6][7][8] and biological properties with potential application on human health [9][10][11]. Anti-inflammatory, analgesic and antimicrobial properties have been attributed to Euphorbia honeys along with the ability to promote wound healing, nevertheless, the majority of works has been focused on the anti-microbial activity [9][10][11], and much less, antioxidant activity [12]. More recently, our team compared the antioxidant activity and some enzyme inhibitory activities of Euphorbia officinarum, E. resinifera plants with those of the respective two monofloral honeys [13].…”
Section: Introductionmentioning
confidence: 99%
“…With an inhibition diameter of 6.67 ± 0.33, 8.33 ± 0.67 and 9 ± 0 for flowers, stems and roots, respectively for the methanolic extract and an inhibition diameter of 7 ± 0, 10.83 ± 0.17 and 12.17 ± 0.17 mm for flowers, stems and roots respectively for ethyl acetate extract ( Farah et al, 2014 ). In an earlier study conducted by our research team, which investigated the antibacterial activity of the same bacterial strains, it was found that 37 samples of E. resinifera honey from the Tadla Azillal region in Morocco demonstrated activity against both tested strains ( Benjamaa et al, 2020 ). These findings may be attributed to the specificity of bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…This species is exclusive to Morocco. Many researchers have documented the pharmacological activity of Euphorbia resinifera extracts, including antioxidant (Boutoub et al 2020;Benrahou et al 2022), antitumoral (Talbaoui et al 2020;Hmidouche et al 2023), antibacterial (Moujanni et al 2017;Talbaoui et al 2020;Benjamaa et al 2020), and antifungal activities (Ourhzif et al 2022).…”
Section: Fidelity Level Index (Fl)mentioning
confidence: 99%